Monodisperse Ternary NiCoP Nanostructures as a Bifunctional Electrocatalyst for Both Hydrogen and Oxygen Evolution Reactions with Excellent Performance. Issue 4 (9th December 2015) - Wang, Chunde; Jiang, Jun; Ding, Tao; Chen, Guihuan; Xu, Wenjing; Yang, Qing
Abstract : Monodisperse ternary NiCoP nanostructures are produced via a facile one‐pot hot‐solution method for the first time. The NiCoP nanoparticles exhibit excellent catalytic activity and durability for both hydrogen evolution reactions and oxygen evolution reactions. This work may promote intensive investigations of such transition‐metal‐phosphide solid solutions for wide potential applications.